Sealed with a Kick: A Case of Posttraumatic Coronary Artery Dissection and Cardiomyopathy - Nithin Gottam; Sule Salami; Mahmoud Othman; James Torey; Howard Rosman; Andrzej Boguszewski (Case Reports in Vascular Medicine)
Blunt chest trauma can lead to a variety of cardiac injuries, one of which is nonatherosclerotic myocardial infarction caused by intimal laceration and thrombotic process activation. Here we present a case of anterior myocardial infarction secondary to blunt trauma involving a kick to the chest.